A Comprehensive Harmonic Analysis of Current-Mode Power Amplifiers - Chiara Ramella (MDPI AG, 2021)
This work presents a comprehensive theoretical analysis of current-mode power amplifiers as a function of input power for different biasing classes under the common simplifying assumption of constant transconductance and hard current cut-off/saturation. Typically, the theoretical analysis of power amplifier performance and behavior are carried out only at maximum output power. However, to achieve high data-rates, modern telecommunication systems adopt signals characterized by a very high peak-to-average power ratio, thus it is useful to analyze the power amplifier behavior as a function of power back-off. Moreover, in many cases, to enhance the efficiency and/or to apply harmonic shaping techniques, a clipped drain-source current, which approaches a square wave, is required. The classical analysis can be extended to low power levels only under the assumption of power-independent conduction angle, which is true only for class-A and class-B amplifiers, and does not take into account possible waveform clipping at maximum current. This work presents a complete theoretical Fourier analysis of FET-based power amplifiers as a function of quiescent drain-source current at any input power level and accounting for the clipped current case, up to the square-wave limit, reorganizing and completing the material that can be found in classical textbooks in the field.